Reconstruction of Agreements for Land and Crops on it as an Instrument of Sharia Economic Justice in Indonesia - Alwan, Muhammad (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2025)
The practice of profit sharing on land and crops in Indonesia still shows an imbalance between landowners and cultivators, mainly due to the non-implementation of the principles of justice mandated by Shariah economic law. Profit-sharing contracts such as muzara'ah and musaqah are essentially designed as instruments for economic equity based on partnership, but in practice, they are often deviated by relationship patterns that tend to be exploitative. This article aims to analyze the regulation of contracts for land and the crops thereon from the perspective of Shariah economic law, and to formulate a reconstruction of the contract concept to align with the principles of justice (al-'adl), benefit (al-maslahah), and the values of Shariah economic law. This research uses a normative juridical method with a statute approach, conceptual approach, and maqāṣid al-syarī‘ah approach. Data were obtained through literature study of primary legal sources such as the Compilation of Shariah Economic Law (KHES) Book II Chapter IV, DSN-MUI Fatwa No. 14/DSN-MUI/IX/2000 concerning Muzara'ah and Musaqah, and Law No. 19 of 2013 concerning Protection and Empowerment of Farmers, as well as scientific literature from the 2019–2024 period. The results show that the regulation of profit-sharing contracts for land and crops in Indonesia is still fragmentary and has not fully adopted the principle of distributive justice in Shariah economic law. Therefore, a reconstruction of the contract concept is needed through the integration of the values of al-'adl (justice), al-maslahah (benefit), and al-amanah (trustworthiness) as outlined in a modern shirkah-muzara'ah based contract model. This model places both parties—the owner and the cultivator—as equal partners in the division of results according to the contribution of capital and labor.